Adhesive-free structural timber panels: a comparison of stiffness in nail-laminated and dowel-laminated timber panels - Minari, Vitor Hugo; Pereira, Marcos Cesar M. [UNESP]; Calil Junior, Carlito (Taylor & Francis, 2024)
Since wood is an ecologically more efficient material than steel or concrete, as it requires less energy to process and sequesters carbon, it has been increasingly studied for the incorporation of structural panels on the world market. Unfortunately, Brazilian culture is a major barrier to overcoming when it comes to building with alternative materials. Against this backdrop, the main objective of this research is to study structural panels made of nail-laminated timber (NLT) and dowel-laminated timber (DLT) based on the experimental analysis of panels produced in the laboratory. This study contributes to the understanding of the structural performance of adhesive-free timber panels, which are emerging as one of the new Engineered Wood Products (EWPs) and can be efficiently used as flooring or roofing solutions. In the case of DLT, besides being glue-free, they are panels that have no other material in their composition apart from the wood itself. Samples of nailed and doweled connections were tested following the Brazilian standard NBR 7190-5 (ABNT, 2022e). Additionally, bending tests were performed on both nailed and doweled panels to assess their modulus of elasticity in both directions and their flexural strength in the primary direction. While DLT offers environmental advantages, the NLT specimens demonstrated greater structural efficiency across all evaluated parameters.
Keywords: adhesive-free timber connection; bending stiffness; engineered wood products; slip modulus of the connection; structural wooden panels